2006
DOI: 10.1177/0115426506021006557
|View full text |Cite
|
Sign up to set email alerts
|

Fostering Coping Skills and Resilience in Home Enteral Nutrition (HEN) Consumers

Abstract: Implications for clinical practice and HEN education, along with suggestions for healthcare providers to foster coping with HEN are provided. An educational manual with self-help suggestions for adult HEN consumers is also available at http://www.copingwell.com.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 28 publications
(31 reference statements)
3
25
0
Order By: Relevance
“…Regardless of length of home PN dependency in the present study, participants perceived that life “could be a heck of a lot worse.” In addition, using downward social comparison (the process of comparing oneself to someone worse off), 65 , 66 participants saw their own situation as better than others who had a physical disability or cancer. These findings are comparable to home enteral nutrition consumers who also noted that home tube feeding was a small challenge when compared to other people's problems 67 …”
Section: Discussionsupporting
confidence: 69%
“…Regardless of length of home PN dependency in the present study, participants perceived that life “could be a heck of a lot worse.” In addition, using downward social comparison (the process of comparing oneself to someone worse off), 65 , 66 participants saw their own situation as better than others who had a physical disability or cancer. These findings are comparable to home enteral nutrition consumers who also noted that home tube feeding was a small challenge when compared to other people's problems 67 …”
Section: Discussionsupporting
confidence: 69%
“…Essential components of the education process include training on feeding tube and access site care, preparation and administration of formula, medication administration, enteral pump operation, monitoring and troubleshooting complications, and emergency care plan and contact information 6 , 8 . ‐ 12 Thompson et al 13 have emphasized the need for clinicians to evaluate the effectiveness of their EN education process, provide comprehensive EN education and patient resources, proceed over more than 1 educational session, and prepare patients and caregivers to resolve foreseeable problems, such as tube occlusion and dislodgement, skin care issues, and psychosocial challenges.…”
Section: Section 11 Transition Of Carementioning
confidence: 99%
“…Flexibility within feeding regimens may alleviate some of the stress that patients have and has the potential to improve the impact of EN on quality of life. Simplifying the EN regimen, minimizing the infusion time, and providing an ambulatory pump or feeding tube that best fits the patient's physical and lifestyle needs may help reduce EN‐associated life disruptions 13 . For some patients with gastrostomy tubes, transition to home may be made easier by employing the syringe/bolus feeding method.…”
Section: Section 11 Transition Of Carementioning
confidence: 99%
“…Thompson et al 22 reported a struggle in the acceptance of feeding tube permanence in some home enteral nutrition consumers. The intention was to capture the patient's experience in its entirety, including removal.…”
Section: Discussionmentioning
confidence: 99%